(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This article presents a comprehensive comparative analysis of the role of the public prosecutor in the criminal justice systems of India, the United States, and the United Kingdom. It explores the distinct functions and responsibilities of prosecutors in these countries, highlighting how their roles are influenced by different legal frameworks. In India, the public prosecutor acts as a minister of justice, ensuring fair proceedings without interfering with police investigations. In contrast, U.S. prosecutors have significant influence in charge framing and plea bargaining, often dominating the judicial process. The UK’s Crown Prosecution Service operates independently, striving to uphold public interest while sometimes constrained by resource limitations. This comparative study underscores the integral role of prosecutors in upholding the law, protecting human rights, and maintaining societal order, despite the varying degrees of government involvement and judicial process across these legal systems. The United Kingdom operates under the Crown Prosecution Service (CPS), which functions independently. Crown prosecutors adhere to a code of conduct, emphasizing the preparation and presentation of cases in court. However, resource limitations occasionally constrain their ability to operate independently. The CPS strives to uphold public interest, ensuring that cases are prosecuted in the best interest of society. Recommendations arising from this study include the need for stronger oversight of prosecutorial discretion in India and the U.S., comprehensive training programs emphasizing ethics and fairness, allocation of adequate resources to the CPS in the UK, and enhanced transparency in prosecutorial decision-making across all three countries. The scope of future research could encompass a broader comparative analysis involving additional jurisdictions, an examination of the impact of technology on prosecutorial roles, an exploration of cultural influences on prosecutorial behavior, and an investigation into mechanisms of accountability for prosecutors.